PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR DAN PROFIL PELAJAR PANCASILA SISWA DI SDN 151 SUKASENANG KOTA BANDUNG - Nur Fahmi Fardila; Uus Toharudin; Sopyan Hendrayana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the effect of using the problem based learning model on learning outcomes and achievement of Pancasila student profiles in class IV students in the 2022/2023 academic year. In this study using a quantitative approach using a research design that is quasi-experimental (Quasi-Experimental Design). The sample of this research was class IVB which consisted of 26 students as the experimental class and class IVA which consisted of 27 students as the control class. The technique of collecting data is through a multiple choice test and a description of the material changing the form of energy and observation sheets as supporting data. The tests used are pre-test and post-test which are used as data on learning outcomes and achievement of the Pancasila student profile towards students. Data analysis techniques were carried out using validation tests, reliability tests, index difficulty level tests, and discriminatory power. Research conducted at SDN 151 Sukasenang, Bandung City, showed that the average post-test score for the experimental class was 88.23, and the average value for the control class was 86.70. By calculating using the Independent sample t-test formula using IBM SPSS Statistics 26 software, the results of the analysis show that tcount = 2.317> ttable = 2.009 and a sig value of 0.025 <0.05. That is, there are differences in the results of the post-test, it can be concluded that the Problem Based Learning (PBL) model significantly influences learning outcomes and achievement of Pancasila student profiles.